2018
DOI: 10.2459/jcm.0000000000000634
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum uric acid affects myocardial reperfusion and infarct size in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: eSUA may affect myocardial reperfusion in patients with STEMI undergoing percutaneous coronary intervention and is associated with larger infarct size and higher long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Thus, finding from animal study cannot necessarily be generalized to species with comparatively low activities of XO. Meanwhile, hyperuricemia is associated with impaired myocardial reperfusion and greater infarct size [ 30 , 31 ], which associated with higher rates of ventricular arrhythmias [ 32 , 33 ]. The present study confirmed these data: patients with hyperuricemia presented with increased troponin I levels, risk of no-reflow and worse LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, finding from animal study cannot necessarily be generalized to species with comparatively low activities of XO. Meanwhile, hyperuricemia is associated with impaired myocardial reperfusion and greater infarct size [ 30 , 31 ], which associated with higher rates of ventricular arrhythmias [ 32 , 33 ]. The present study confirmed these data: patients with hyperuricemia presented with increased troponin I levels, risk of no-reflow and worse LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…STEMI was diagnosed based on two of the three following criteria: (1) typical signs of ST‐segment elevation in two contiguous leads on electrocardiogram; (2) typical signs of elevated cardiac biomarkers, including troponin, creatine kinase and creatine kinase‐myocardial band (CK‐MB), which were increasing proportionally; and (3) typical chest pain symptoms. SUA was measured on admission with the same method, and patients were divided into two groups based on an SUA cut‐off level of 6.8 mg/dL, as previously reported 14,15 …”
Section: Methodsmentioning
confidence: 99%
“…Although an elevated SUA may induce larger acute infarct size, the study concluded that there is no further impairment in the repairing phase as infarct size shrinkage is similar compared with patients who have normal SUA levels. 58 Kojima et al 59 suggested that patients with hyperuricemia with an AMI have a higher rate of left ventricular systolic and diastolic dysfunction, as well as MACE (including heart failure, death), possibly because UA could increase oxidative stress and inflammation inducing cardiomyocyte apoptosis with further myocardial remodeling.…”
Section: Uric Acid and Acute Myocardial Infarctionmentioning
confidence: 99%